Internationalisation business processes in an under-supported policy contexts: evidence from Italian SMEs. Issue 5 (5th April 2020) - Jafari-Sadeghi, Vahid; Dutta, Dev K.; Ferraris, Alberto; Del Giudice, Manlio
Abstract : Purpose: The main objective of this research was to identify the key critical determinants of internationalisation business processes that entrepreneurs adopted in under-supported policy contexts. Design/methodology/approach: This research utilised a case-study design, incorporating multiple case examples, applying non-probability purposive selection criteria. A total of five in-depth, structured 90-min to two-hour case interviews were conducted with Italian entrepreneurs, in which four out of the five cases selected are goods-oriented, and one is services oriented. Findings: Regarding internal entrepreneurial motives, four crucial determinants were recognised: (1) Making more profit, (2) Expanding market, (3) Personal tendency to export and (4) Obtaining social respect. Regarding external networking capabilities, two key factors were identified: (1) Developing relationships with an international partner or representative and (2) Maintaining relationships with industry-relevant authorities. Research limitations/implications: The data gathered for this paper depends on self-announcing, expanding the likelihood of being one-sided for social desirability answers. The sample of research is also limited to small and medium businesses and has covered a limited number of companies. Originality/value: An under-supported policy context forces international entrepreneurs to make their own arrangements and tailor their business process through personal initiative and interactions with network partners. Taking advantage of field-based data, this paper is probably one of the earliest research studies to identify several internal and external factors impacting on firm internationalisation business processes in the low policy support context for entrepreneurship.